SIPANI: Expert System As Smart Farming Application Web Based: SIPANI: Sistem Pakar Tani Aplikasi Smart Farming Berbasis Website - Agnes Manuhutu, Melda; Anggreyani Widya Astuty, Putu; Wattimena, Lanny (Dinamisia : Jurnal Pengabdian Kepada Masyarakat, 2025)
The Dharma Sentosa Farmers Group has been developing the dragon fruit growing business since 2015. The Dharma Sentosa Farmers Group sometimes employs young farmers who do not have sufficient knowledge about how to care for and handle plants that are attacked by pests. This causes a decrease in the yield or quality of dragon fruit during harvest. Apart from that, the high competition in the dragon fruit farming business can provide challenges for farmer groups in marketing their crops. The resulting product can be less competitive in terms of visibility and attractiveness compared to competitors who are more aggressive in promotion. The method of implementing activities is socialization, training, application of technology, mentoring, and evaluation as well as program sustainability. Based on the activity evaluation, the average percentage of dragon fruit quality measurements is 84.8% and is in the very good range based on the average percentage interval. Based on the results of the interview, the Chairman of the Dharma Sentosa Farmers Group said that using the SIPANI Store opens up opportunities for his business to get more markets and sell more of the harvests he gets. The turnover generated after using the SIPANI Store is 3 quintals.